Analysis of Groundwater Quality in A Coastal Area: Case Study of Durung Village, Aceh Besar Regency: Analisis Kualitas Air Tanah di Wilayah Pesisir: Studi Kasus Gampong Durung, Kabupaten Aceh Besar - Tanjung, Maulina; Hartati, Diah Vitaloka; Arfah, Mahbub (ALTAIR: Jurnal Transportasi dan Bahari, 2024)
Groundwater quality in coastal areas is responsive due to the interaction of fresh water with seawater. Groundwater quality monitoring studies in coastal area needs to be done regularly to prevent natural disasters and clean water crises in the future. In this study, measurements of groundwater physics parameter were carried out, i.e. electrical conductivity to analyze groundwater quality. The interpolation method based on Geographic Information Systems (GIS) was used to obtain values ​​between each sample point to produce a spatial distribution map of groundwater quality over the research location. The results of the study showed that groundwater quality in the coastal area of ​ Durung Village was generally still quite good with conductivity values ​​between 689 - 3,391 µS/cm. However, for the locations which is nearby the coast such as in the location of Malahayati Merchant Marine Polytechnic, it was indicated that it had been contaminated by seawater with the highest conductivity values between 5,763 – 6.270 µS/cm.